KONTRIBUSI KEHARMONISAN KELUARGA TERHADAP MOTIVASI BELAJAR SISWA - Kharisma Novitasari; Raudah Zaimah Dalimunthe; Bangung Yoga Wibowo (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
The purpose of this study was to find out how the relationship between family harmony with the learning motivation of class X students of SMA Negeri 6 Serang City. This type of research is quantitative with correlational methods. The population in this study numbered 396 and to calculate the number of samples using the Slovin formula and produce a sample of 198 students. Data collection technique using random sampling. Data analysis using correlation analysis. Based on the results of the correlation test, the result of r is 0.426 with a significance level of 0.00 (p <0.05), which can be concluded that there is a positive relationship between family harmony and learning motivation. The effect of family harmony on learning motivation can also be seen from the results of the determination coefficient R = 0.181, and it can be concluded that the effective contribution made by the family harmony variable to learning motivation is 18.1%.